Michael Tolliver lives - Maupin, Armistead (New York HarperCollinsPublishers, 2007)
Michael Tolliver, the sweet-spirited Southerner in Armistead Maupin's classic Tales of the City series, lives on in this novel about growing older joyfully. Almost twenty years after ending his saga of San Francisco life, author Maupin revisits his all-too-human hero, letting the 55-year-old gardener tell his own story. Having survived the plague that took so many of his friends and lovers, Michael has learned to embrace the random pleasures of life, the tender alliances that sustain him in the hardest of times. This book follows its protagonist as he finds love with a younger man, attends to his dying fundamentalist mother in Florida, and finally reaffirms his allegiance to a wise octogenarian who was once his landlady. This stand-alone novel is accessible to new readers, while fans of Tales of the City will find a reassuring number of familiar faces.--From publisher description.
UCWS-2015-G-2252 donated by Prof. Eric Julian Manalastas
Keywords: City and town life -- California -- San Francisco -- Fiction; San Francisco (Calif.) -- Fiction